Failure behaviors of 3D braided composites with defects in different locations under low-velocity impact compression. Issue 1 (January 2022) - Guo, Jinhui; Sun, Baozhong; Gu, Bohong; Zhang, Wei
This paper aims to investigate the effects of the impurity defects in different locations on the transverse compressive behaviors of three-dimensional (3D) braided carbon fiber/epoxy composites under low-velocity impact. The composites with defects in different locations were prepared by placing polytetrafluoroethylene particles at the bottom surface, corner and center parts, respectively. The compression test was implemented with the drop-weight impact method. The failure morphologies were characterized using high-speed photography and micro computed tomography (Micro-CT). A mesoscale finite element model considering the defect was developed to enhance the physical understanding of the compression process. It is found that defects located at the corner zone and the central zone have a greater impact on the compression behavior of the 3D braided composite than the defect located at the bottom surface part. The defects at the corner and center zones reduce the compressive strength of the composite, increase the failure area, and cause severe damage to both the yarn and resin. In addition, the defect causes local stress concentration on the surrounding yarns. The defects in different locations cannot change the main shear failure mode of the 3D braided composite. It is shown that great attention should be given during the manufacturing or detection process to avoid such a deterioration effect of defects located in those zones on composite strength.